Home-To-Home Media Streaming System Based on Adaptive Fast Replica - Vasanth Raj, P.T.; Vijayaraj, A (International Journal of Computer Sciences and Engineering, 2019)
Users can enjoy High Definition (HD) video content instead of being satisfied with Standard Definition (SD) video content. Such HD-grade User Created Content (UCC) streaming requires significant bandwidth and download time due to their large sizes. However, the established Internet service environment does not ensure sufficient network bandwidth for directly streaming such high quality content between members of a family or group in different Universal Plug and Play (UPnP) enabled home networks. Hence we design a system that enables a source media server to stream high quality content to multiple renderers in physically separated homes through peer-to-peer overlay paths established between home servers with content distribution and QoS device capability.